Penyisihan Logam Pb Air Lindi Tpa Muara Fajar Menggunakan Tanah Lempung Dengan Metode Pertukaran Ion - Resty Maiyola; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Landfill leachate treatment at Muara Fajar there are still many obstacles. At the pool fourth treatment, Metal Pb and Cu and hardness concentration is high, so it needs further treatment before being discharged into the environment. The purpose of this research is an alternative water treatment technologies for Muara Fajar landfill leachate, in order that the leachate does not pollute the environment. This research uses ion-exchange column with a clay medium for lower concentrations of Pb, Cu and hardness with high of colom 1.2 m and 2 inches diameter with clay -15 + 20 mesh size, the variation used is the bed height 40, 60, and 80 cm and the discharge flow 80,100, and 120 ml / min. The results of analysis of effluent concentration of Pb metal is 0.41 mg / L, Cu, 0.51 mg / L, and 283 mg / L for hardness. This concentration has reached the quality standard limits the Minister of Environment Decree No. 51 Year 1995 for bed height and discharge flow is 80 cm and 80 ml / min with a CEC of 80 meq / 100g.Keyword : Bed height, Clay, Discharge flow, Ion Exchange, Landfill Leachate.